2018
DOI: 10.1002/jcph.1132
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C Is a More Reliable Biomarker for Determining eGFR to Support Drug Development Studies

Abstract: Glomerular filtration rate (GFR) is routinely used as a surrogate endpoint for the development of investigational drugs in clinical trials. GFR and staging of chronic kidney disease are typically assessed by measuring the concentration of endogenous serum biomarkers such as albumin and creatinine. However, creatinine is subject to high biological variability, and levels of creatinine do not rise until nearly 50% of kidney function is damaged, leading to inaccurate chronic kidney disease staging and false negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 64 publications
0
38
1
Order By: Relevance
“…Cystatin C is a sensitive marker for renal impairment [33]. In this study, no significant difference in the change of sCr within 1 month was found in both TDF and ETV groups, while there was significant difference in the change of cystatin C in both groups.…”
Section: Discussioncontrasting
confidence: 49%
“…Cystatin C is a sensitive marker for renal impairment [33]. In this study, no significant difference in the change of sCr within 1 month was found in both TDF and ETV groups, while there was significant difference in the change of cystatin C in both groups.…”
Section: Discussioncontrasting
confidence: 49%
“…Serum Cys-C indicates the real-time functional state of the kidney. It has been suggested to be an endogenous marker for predicting the early and accurate diagnosis of AKI [ 22 24 ]. We observed that Cys-C was detected at high levels in LPS-exposed mice, identifying renal dysfunction in the early stages of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the serum Creat concentrations, CysC was not affected by intra-variabilities such as gender and muscle mass, providing a more accurate measure of renal function [30, 31]. Evidence exists of the significant association of higher serum levels of CysC with increased microalbuminuria and lower GFR, which could reflect renal damage and impaired renal function [30].…”
Section: Discussionmentioning
confidence: 99%